2015
DOI: 10.20473/mog.v23i3.2077
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Topikal Ekstrak Daun Pepaya (Carica papaya) pada Hewan Coba Mencit (Mus musculus) Bunting Meningkatkan Kepadatan Kolagen Jaringan Vagina

Abstract: Tujuan: Menganalisis pengaruh pemberian gel ekstrak air daun pepaya terhadap kepadatan kolagen jaringan vagina pasca melahirkan pada hewan coba mencit saat bunting.Bahan dan Metode: Desain penelitian randomized post test only control group,dilakukan di Departemen Embriologi Veteriner, Fakultas Kedokteran Hewan, Universitas Airlangga, pada bulan April-Juni 2015. Terdapat empat kelompok, masing-masing kelompok terdiri dari 8 mencit bunting. Kelompok kontrol (tanpa perlakuan) dan kelompok perlakuan berupa pemberi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of research by Suni et al (2017) concluded that boiled water of papaya leaves has an inhibitory effect on C. albicans. Djunaidi et al (2015) found that topical administration of concentrated papaya leaf extract 5% during pregnancy in mice increases post-partum vaginal tissue collagen density. Research by Nilofer and Chenthamarai (2021) concluded that C. papaya leaf extract contains antifungal compounds that can inhibit C. albicans.…”
Section: Vaginal Dischargementioning
confidence: 96%
“…The results of research by Suni et al (2017) concluded that boiled water of papaya leaves has an inhibitory effect on C. albicans. Djunaidi et al (2015) found that topical administration of concentrated papaya leaf extract 5% during pregnancy in mice increases post-partum vaginal tissue collagen density. Research by Nilofer and Chenthamarai (2021) concluded that C. papaya leaf extract contains antifungal compounds that can inhibit C. albicans.…”
Section: Vaginal Dischargementioning
confidence: 96%